Emerging Roles of the Membrane Potential: Action Beyond the Action Potential - Abdul Kadir, Lina; Stacey, Michael; Barrett-Jolley, Richard (Frontiers in Physiology, 2018)
Whilst the phenomenon of an electrical resting membrane potential (RMP) is a central tenet of biology, it is nearly always discussed as a phenomenon that facilitates the propagation of action potentials in excitable tissue, muscle and nerve. However, as ion channel research shifts beyond these tissues, it became clear that the RMP is a feature of virtually all cells studied. The RMP is maintained by the cell’s compliment of ion channels. Transcriptome sequencing is increasingly revealing that equally rich compliments of ion channels exist in both excitable and non-excitable tissue. In this review, we discuss a range of critical roles that the RMP has in a variety of cell types beyond the action potential. Whereas most biologists would perceive that the RMP is primarily about excitability, the data show that in fact excitability is only a small part of it. Emerging evidence show that a dynamic membrane potential is critical for many other processes including cell cycle, cell-volume control, proliferation, muscle contraction (even in the absence of an action potential) and wound healing. Modulation of the RMP is therefore a potential target for many new drugs targeting a range of diseases and biological functions from cancer through to wound healing and is likely to be key to the development of successful stem cell therapies.